2018
DOI: 10.1051/0004-6361/201832787
|View full text |Cite
|
Sign up to set email alerts
|

Search for Galactic runaway stars using Gaia Data Release 1 and HIPPARCOS proper motions

Abstract: Context. The first Gaia Data Release (DR1) significantly improved the previously available proper motions for the majority of the Tycho-2 stars. Aims. We wish to detect runaway stars using Gaia DR1 proper motions and compare our results with previous searches. Methods. Runaway O stars and BA supergiants were detected using a 2D proper motion method. The sample was selected using Simbad, spectra from our GOSSS project, literature spectral types, and photometry processed using the code CHORIZOS. Results. We dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 87 publications
(101 reference statements)
7
53
3
Order By: Relevance
“…Although this agrees with runaway fraction for O stars in a 10 3.5 M cluster (Oh & Kroupa 2016), it is not universal and observational data indicates that this fraction can be significantly lower with variations with stellar type. Maíz Apellániz et al (2018) estimated the fraction at 10 − 12% for the O stars and ∼ 6% for B stars, which is also in agreement with those from Eldridge et al (2011) when correcting for completeness. The results shown here could therefore overestimate the impact of runaway stars.…”
Section: Limitations Of the Modelsupporting
confidence: 77%
See 1 more Smart Citation
“…Although this agrees with runaway fraction for O stars in a 10 3.5 M cluster (Oh & Kroupa 2016), it is not universal and observational data indicates that this fraction can be significantly lower with variations with stellar type. Maíz Apellániz et al (2018) estimated the fraction at 10 − 12% for the O stars and ∼ 6% for B stars, which is also in agreement with those from Eldridge et al (2011) when correcting for completeness. The results shown here could therefore overestimate the impact of runaway stars.…”
Section: Limitations Of the Modelsupporting
confidence: 77%
“…While a collisionless approximation is valid on galactic scales, star-star interactions drive the internal dynamics of dense star clusters. As a result, some fraction of OB stars are kicked out of their natal star clusters with velocities large enough to move them out of the dense star forming gas before exploding as SNe (e.g., Gies & Bolton 1986;Gies 1987;Stone 1991;Hoogerwerf et al 2000;Schilbach & Röser 2008;Jilinski et al 2010;Silva & Napiwotzki 2011;Maíz Apellániz et al 2018). Simulation of clusters (e.g., Oh & Kroupa 2016) reveal that such velocity kicks originates from gravitational interactions (Poveda et al 1967), including the disruption of binaries through SNe (Blaauw 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Testori et al (2006) mention that Hoogerwerf et al (2001) identified a B-type runaway star (HD 64760, HIP 38518), and suggested it was ejected in a binary-supernova scenario that took place in the Vela OB2 region. The identification of hypervelocity stars from Gaia data (Renzo et al 2018;Marchetti et al 2018;Maíz Apellániz et al 2018;Irrgang et al 2018) might tell us whether other such objects are compatible with an origin inside the IVS. A full dynamical modelling of the orbits of hypervelocity stars and nearby open clusters is beyond of the scope of this study, but should be possible based on the 3D velocities of these objects (Soubiran et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SB1. McSwain et al (2004) determined the SB1 orbit of this γ-ray binary, which is also a runaway star (Maíz Apellániz et al 2018b). We classified it as ON6 V((f))z in GOSSS III.…”
Section: Sagittarius-sagittamentioning
confidence: 99%
“…SB1?. Underhill & Matthews (1995) calculated a SB1 orbit for this runaway star (Maíz Apellániz et al 2018b). The orbit has not been confirmed and it is possible that the radial velocity variations are caused by pulsations.…”
Section: Sagittarius-sagittamentioning
confidence: 99%